"How did that happen?" Public responses to women with mobility disability during pregnancy. Issue 3 (July 2015) - Iezzoni, Lisa I.; Wint, Amy J.; Smeltzer, Suzanne C.; Ecker, Jeffrey L.
Abstract: Background: Little is known about current societal attitudes toward women with significant mobility disability who are visibly pregnant. Objective: To use qualitative descriptive analysis methods to examine perceptions of women with significant mobility disability about how strangers reacted to their visible pregnancies. Methods: In late 2013, we conducted 2-h telephone interviews with 22 women with significant mobility difficulties who had delivered babies within the prior 10 years. The semi-structured, open-ended interview protocol addressed wide-ranging pregnancy-related topics, including statements from strangers. Most participants were recruited through social networks, coming from 17 states nationwide. We used NVivo to sort the texts for content analysis. Results: The women's mean (standard deviation) age was 34.8 (5.3) years; most were white, well-educated, and higher income, although half had Medicaid during their pregnancies; and 18 used wheeled mobility aids. Eighteen women described memorable interactions with strangers relating to their pregnancies or newborn babies. Strangers' statements fell into six categories: (1) curious; (2) intrusively and persistently curious; (3) hostile, including concerns that taxpayers would end up supporting the mother and child; (4) questioning woman's competence as a potential parent; (5) oblivious, not recognizing visible pregnancy or motherhood; and (6) positive. Many women reported strangers asking how their pregnancy had happened. The women doubted that visibly pregnant women without disabilities evoke the same reactions from strangers. Conclusions: Women with mobility disability who are visibly pregnant may perceive reactions from strangers that appear intrusive. Planning ahead for handling such encounters could reduce the stresses of these interactions.